Severity and recovery of post-fire vegetation cover using satellite images and burned area indices in Cajamarca (Peru) - Cubas Sanchez, Jefferson Anthony (2026)
Background Assessing the severity of forest fires allows us to identify changes that compromise the natural regeneration capacity of vegetation. In this study, we evaluated the severity and recovery of vegetation after a fire using Sentinel-2 satellite images for the Cajamarca department in northeastern Peru. Hot spots were downloaded from the Fire Information for Resource Management System (FIRMS). This allowed us to identify eight groups with an area >100 hectares, heat intensity >100 Fire Radiative Power (FRP), and the presence of trees. By applying the Normalized Burn Ratio (NBR) and the Normalized Difference Vegetation Index (NDVI), the levels of extreme, high, medium, and low severity were determined, as well as the recovery of vegetation before and after the fire events. Results and Conclusions The results indicated that 71.02% of the evaluated territory had low severity, 21.95% had medium severity, 6.41% had high severity, and 0.65% had extreme severity, indicating a prevalence of medium to low severity in the study area. The fires that occurred had similar NDVI levels in the pre-fire stage; however, after the fire, a progressive recovery of vegetation was observed in the study area. This highlights the application of spectral indices to assess the impact and regrowth of vegetation after the development of fires.